Impacto de la capacitación en los niveles de satisfacción laboral, aprendizaje, desempeño y desarrollo de carrera individual en el personal nacional (NRS) de las aéreas de investigación del Centro Internacional de Agricultura Tropical CIAT- año 2010. Tesis (Administrador de Empresas) - Alonso Realpe, L.A.; Matta Pantoja, MI (Universidad del Valle, 2011)
This graduate work seeks to determine whether the training as an independent variable is related to the partners on levels of job satisfaction, learning, performance and individual career development, these taken as dependent variables. The research is correlational transactional type, with correlational hypothesis, using the questionnaire as an instrument of data collection, a sample of 56 employees, also is the chi-square X2 to determine the correlation betwe